2008
DOI: 10.1007/s00441-008-0699-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan substratum holds mesenchymal stem cells in slow-cycling mode by prolonging G1 phase

Abstract: We examined, in vitro, whether hyaluronan induces slow cycling in placenta-derived mesenchymal stem cells (PDMSCs) by comparing cell growth on a hyaluronan-coated surface with cell growth on a tissue-culture polystyrene surface. The hyaluronan-coated surface significantly downregulated the proliferation of PDMSCs, more of which were maintained in the G(0)/G(1) phases than were cells on the tissue-culture polystyrene surface. Both PKH-26 labeling and BrdU incorporation assays showed that most PDMSCs grown on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
5
16
0
1
Order By: Relevance
“…Our evaluation of the effect of HA concentrations on MSCs indicates that HA affected MSC proliferation in a dose-dependent manner. Data in the literature shows that the addition of small concentrations of low molecular weight HA stimulates MSC proliferation [42,43], while the same concentration of high molecular weight HA appears to inhibit the cells [44,45]. Our experiments with high molecular weight HA in a 2D system did not show any significant effect on MSC proliferation (data not shown) while cells cultured on a calcite scaffold in a 3D system in the presence of HA of various concentrations displayed a reduction in cell number.…”
Section: Effect Of Ha Concentration On Msc Proliferationmentioning
confidence: 43%
“…Our evaluation of the effect of HA concentrations on MSCs indicates that HA affected MSC proliferation in a dose-dependent manner. Data in the literature shows that the addition of small concentrations of low molecular weight HA stimulates MSC proliferation [42,43], while the same concentration of high molecular weight HA appears to inhibit the cells [44,45]. Our experiments with high molecular weight HA in a 2D system did not show any significant effect on MSC proliferation (data not shown) while cells cultured on a calcite scaffold in a 3D system in the presence of HA of various concentrations displayed a reduction in cell number.…”
Section: Effect Of Ha Concentration On Msc Proliferationmentioning
confidence: 43%
“…When we cultured PDMSCs on substrata containing more than 3 μg/cm 2 hyaluronan, their adherence rates were reduced (Liu et al 2008), either because of the antiadhesive property of hyaluronan (Pavesio et al 1997) or because of a lack of hyaluronan receptors on the membrane. Previous studies have reported that CD44 overexpression induced a dramatic increase in hyaluronan-mediated cell adhesion (Zhu and Bourguignon 1996) and increased hyaluronan-binding avidity (Lesley et al 2000).…”
Section: Discussionmentioning
confidence: 97%
“…Because PDMSCs grown on a hyaluronan-coated surface are slow cycling (Liu et al 2008), even when seeding density is doubled and tripled (Fig. 3), and proliferate less than cells grown on a polystyrene surface, they are able to resist doxorubicin.…”
Section: Discussionmentioning
confidence: 98%
“…The identification of hyaluronan in many locations where stem cells are present raised the possibility that hyaluronan influences these potent cells. Indeed, emerging studies [46] have proven the veracity of this hypothesis, and hyaluronan is now being studied as a key component that may be manipulated to induce desired stem cell behaviors.…”
Section: Hyaluronan Propertiesmentioning
confidence: 99%